2022
DOI: 10.1002/pssa.202200262
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ion Vacancy Migration on Short‐Circuit Current of Perovskite Solar Cells

Abstract: For perovskite solar cells (PSCs), the effect of ion vacancy motion on the short‐circuit current (Jsc) in the reverse and forward J–V scans is investigated. To reveal its mechanism, all the components of current (carrier current, ionic current, displacement current) at the short‐circuit working point are calculated and the action of mobile ion vacancy on them is explored. By adjusting the parameters determining the ion vacancy mobility μI, the effect of parameter μI on Jsc is discussed. The finding provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is observed that the value of V OC and J SC in the forward scan and reverse scan differ and follow the trend reported by Lin. [ 17,18 ] As reported by Lin, the ion vacancies migrate within the Debye layers due to the applied bias voltage. This migration affects the ionic charge accumulation and screens the in‐built field by the space charge effect, thereby, giving rise to the scan‐dependent value of V OC and J SC .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It is observed that the value of V OC and J SC in the forward scan and reverse scan differ and follow the trend reported by Lin. [ 17,18 ] As reported by Lin, the ion vacancies migrate within the Debye layers due to the applied bias voltage. This migration affects the ionic charge accumulation and screens the in‐built field by the space charge effect, thereby, giving rise to the scan‐dependent value of V OC and J SC .…”
Section: Resultsmentioning
confidence: 86%
“…As a result, a negligible hysteretic effect is observed. Further, Lin [17,18] extended the work to observe the role of the rate of voltage sweep on the solar cell performance parameters such as open-circuit voltage and short-circuit current. He showed that by tuning the rate of voltage sweep between 10 À5 and 10 5 Vs À1 , the mobility of the ionic vacancy gets modified which, in turn, directly affects the value of open-circuit voltage and short-circuit current.…”
Section: Introductionmentioning
confidence: 99%
“…The radiative recombination coefficient is 2 × 10 −17 m 3 /s. The mobile ions concentration and mobility are set to 5 × 10 23 m −3 and 1 × 10 −14 m 2 V −1 s −1 , respectively [20,[47][48][49][50]. We use a uniform carrier generation rate of 3.3 × 10 27 m −3 s −1 in the perovskite layer.…”
Section: Theory and Modelingmentioning
confidence: 99%
“…The film formed by the quantum dots synthesized by them as ligands is not dense and uniform enough, and the resulting defects will block the injection of quantum dots into the luminescent layer, which will greatly affect the combination of electrons and holes in the luminescent layer, thus leading to low fluorescence quantum efficiency and stability. Therefore, it is necessary to find suitable solvents to produce more pure quantum dots, or improve the quality of the film formation of quantum dots through other strategies such as surface passivation [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%